Normal sonographic dimensions for liver, spleen and kidneys in healthy South West Nigerian children-a pilot study (2015)
Ultrasonography measurement of abdominal organ dimensions in children of all ages is utilized in the monitoring of abdominal organ growth pattern, diagonosis and follow-up of patients with a variety of diseases.Base line references values are necessary to determine from the m=normal in pathological states. These values are well established in the developed countries but local reference levels are sparse in this environment. This is a descriptive prospective pilot study done at Ibadan, Nigeria. One hundred and twenty-nine clinically healthy nursery and primary school children, aged between 3 and 10 years consisting of 74 females and 55 males were recruited into the study. Consent was sought from the school authorities and more importanantly from the parents/care givers through letters written through the school authorities. Those pupils whose parents/ care givers gave consent were included in the study. The age of each child was documented in months. Height was measured in meters using a measuring tape with child standing against a vertical wall. Weight was also measured using a ZT standing weighing scale. EAch child underwent abdominal ultrasound evaluation and measurement of liver, spleen and renal diamenters. These parameters were recorded on a prepared data sheet.